Multiple confluent reddish nodules - Thiago Jeunon; Palmira Assis de Jesus Barreto Rodrigues; Thiara Cristina Guimarães Rocha; Marina de Oliveira Bezerra; Antônio Carlos Francesconi do Valle (Mattioli1885, 2013)
00